(untitled) (J. Numer. Anal. Approx. Theory, 2023)
Book review for: Gabriele Ciaramella, Martin J. Gander, Iterative Methods and Preconditioners for Systems of Linear Equations, SIAM, Philadelphia, 2022, X + 275 pp., ISBN 978-1-611976-89-2 (paperback), ISBN 978-1-61197-690-8 (ebook). Part of the Fundamentals of Algorithms series. Reviewed by M. Nechita. Yutaka Yamamoto, From Vector Spaces to Function Spaces. Introduction to Functional Analysis with Applications, SIAM, Philadelphia, 2012, XIV + 268 pp., ISBN 978-1-61197-230-6 (paperback), ISBN 978-1-61197-231-3 (ebook). Part of the Other Titles in Applied Mathematics series. Reviewed by R. Precup.